UNDERSTANDING THE STRUCTURE OF SCIENTIFIC WORK: BASIC TRAINING IN SCIENTIFIC JOURNAL WRITING TECHNIQUES FOR GRADUATE LEVEL STUDENTS - Suprianto, Bambang; suhendra, Suhendra (Universitas Airlangga, 2024)
Basic training in scientific journal writing techniques is an important activity for undergraduate students in understanding the structure of scientific work. This research aims to investigate the impact of this training on improving students' writing skills. The training duration is one day with a total of 3 hours of intensive training. The number of participants involved in this research were 30 undergraduate students from various study programs. The training includes material on the structure of scientific work, effective writing techniques, and the correct use of references. After the training, participants are evaluated through a writing test to measure the improvement of their writing skills. Evaluation results showed significant improvements in participants' ability to organize information, construct coherent arguments, and cite references correctly. This training proves that with a good understanding of the structure of scientific papers and proper writing techniques, undergraduate students can improve their writing skills significantly. The implication of this research is the importance of providing scientific journal writing training to students to prepare them to face academic and professional demands in the future.